Manifestation of leech infestation as severe gastrointestinal bleeding in a 3-year-old boy: a case report and review of the literature - Hamid Reihani; Ali Ghanei-Shahmirzadi; Sara Salehi; Narges Ansari-Charsoughi; Fereshteh Karbasian; Mohammad-Hadi Imanieh (BMC, 2022)
Abstract Background Leeches are a class of hermaphroditic parasites that can attach to various body parts and start sucking blood. Gastrointestinal (GI) bleeding due to leeches is a rare phenomenon that is more common in less developed countries. Common symptoms include melena, hematemesis, pallor, weakness, and fatigue. Due to the similar symptoms of this issue to the main differential diagnoses of GI bleeding in pediatrics, such as diarrhea, constipation, diverticulitis, esophagitis, and anal fissures, it is challenging to differentiate it from the rest. Case presentation We present a three-year-old boy who was transferred to our center with hematemesis, tarry stool, and a drop in hemoglobin level. He finally was diagnosed with a leech in his stomach. Conclusions In less developed counties, the inability to reach safe drinking water, swim in lakes or springs, and inadequate awareness of public health information among individuals can be risk factors for leech infestation.